Evaluation of productivity and operating cost of laser drilling process – a case study - Sarfraz, Shoaib; Shehab, Essam; Salonitis, Konstantinos (IOS Press, 2018)
Laser drilling is a non-conventional machining process which is widely used in automotive, electronics and aerospace sectors to produce holes in diverse range of materials. Different types of lasers and methods are available to produce various hole geometries. Big number of researchers have examined several ways to enhance the performance of this process by investigating different process parameters and drilling methods, that seek improvement of the drilled hole quality. Whereas, productivity and operating cost are also important factors which need to be evaluated along with drilled hole quality. Reducing the drilling time can improve productivity and the selection of a suitable laser can save operating cost which will benefit laser processing industries in this global competitive environment. A case study was performed using different lasers for single pulse and percussion drilling. A significant improvement in productivity was observed with the use of a high power laser that is subject to high operating cost.
Keywords: Laser drilling; operating cost; productivity; drilling time